The origin and evolutionary history of the turlough form of Ranunculus repens - Murphy, Susan (Trinity College (Dublin, Ireland). Department of Botany, 2004)
Turloughs are temporary lakes that occur in karstic limestone areas predominantly in the West of Ireland. They generally flood with groundwater in Autumn and empty through swallow holes in late Spring. This strong ecological gradient allows scope for adaptation of the plant populations that inhabit this environment. Turloughs harbour a morphologically distinct from of the clonal species Ranunculus repens (Ranunculaceae); this form has more dissected and glabrous leaves than the typical broad-leaved form. The main aim of this thesis was to determine whether these apparent differences in leaf shape had an underlying genetic basis potentially induced by the turlough environment.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin